STUDY OF SEDIMENT TRANSPORT AT RIVERS IN SUMATERA SELATAN (Enim River, Lematang River, Lakitan River and Batanghari Leko River) - (NIM 25005041), SARWAN
Some of sediment transport calculation methods have been applied by the rivers where exist in Indonesia. The total sediment transport formulas which applied are Yang's method, Ackers and White, Einstein, Engelund and Hansen, Shen and Hung, Laursen, Leo Van Rijn, Colby's, Karim and Kennedy's and Chang, Simon and Richardson's. Some of the rivers that would be observe for this case are Enim river, Lematang river, Lakitan river and Batanghari Leko river. From the calculation we found the total sediment transport capacity for each river, then compared by the real data. Obviously, there are only some methods that appropriately compatible which applied for sediment load calculation by Enim river, Lematang river, Lakitan river and Batanghari Leko river. The one of compatible calculation for enim river is only Einstein metod, for Lematang river is only Acker and White method, for Lakitan river the compatible method is Yang's method and then for the last one, a compatible calculation for Batanghari Leko is Yang's method.